Penerapan Model Discovery Lerning untuk Meningkatkan Keterampilan Berpikir Kritis dalam Pembelajaran Tematik Muatan IPA pada Siswa Sekolah Dasar 007 Bangkinang - Eno Eria Putri; Sumianto Sumianto; Yusnira Yusnira (MODELING: Jurnal Program Studi PGMI, 2023)
This study aims to improve the critical thinking skills of fitth grade students at SDN 007 Bangkinang for the academic year 2022/2023, totaling 22 students. This research method is Classroom Action Research (CAR) which is carried out in two learning cycles. Each cycle consists of two meetings and four stages of learning namely: planning, implementation, observation, and reflection. The time of the research was carried out in Desember 2022. Data collection techniques were in the form of documentation, observation and tests. The research instrument was in the form of observation sheets (observation sheets of teacher activities and student activities), test sheet evaluation questions, and documentation. While the data analysis techniques in the form of qualitative analysis and quantitative analysis. The results of the critical thinking skills of fifth grade studentss at SDN 007 Bangkinang in pre-action with an average score of 53.40 with a learning mastery percentage of 36%. In the first cycle of the first meeting, the average score was 71.13 with a learning completeness percentage of 45% and in the first cycle of the second meeting, the average value was 75.40 with a learning mastery percentage of 64%. In cycle 2, the first meeting also increased with an average value of 80.59 with a learning completeness percentage of 77%, and in cycle 2, the second meeting increased again with an average value of 87.22 with a learning completeness percentage of 86%. Thus, it can be concluded that the application of the Discovery Learning model can improve the critical thinking skills of fifth grade students at SDN 007 Bangkinang.